Research on the Comprehensive Regionalization of Education and Urbanization based on Multi-scale Spatial Clustering - Xiao, Xiang; Guo, Jianying; Nie, Linxuan; Lin, Xuanzhen; Yu, Wenhui; Huang, Chenxi (Journal of Educational Research and Policies, 2025)
Taking Yunnan’s compulsory education as the research object, with the new urbanization as an important foundation for regional development, this study constructs a comprehensive evaluation index system of “regional background-education status” and uses linear weighted model and multi-scale spatial unit division method to carry out a districting study of Yunnan’s compulsory education. The results show that Yunnan’s education-urbanization can be divided into 6 first-level districts and 19 second-level districts. The key factor causing the regional-educational disparity between the first-level districts is the diversity of student sources and the new urbanization.